Noninvasive Coronary Flow Reserve Evaluation of Coronary Stenosis Detected by Multislice Computed Tomography: A Value Added Proposition?. Issue 3 (24th January 2013) - Koshy, Santhosh K.G.; Khouzam, Rami N.; Govindarajan, Gurushankar
<x xml:space="preserve">Abstract</x> See Article on Page 338